Pharmacologic prophylaxis and risk factors for intraoperative floppy-iris syndrome in phacoemulsification performed by resident physicians - Chen, Andrew A; Kelly, John P; Bhandari, Anuja; Wu, Michael C (Journal of cataract and refractive surgery, 2010)
To determine the incidence of intraoperative floppy-iris syndrome (IFIS) in patients taking tamsulosin who had surgery by resident physicians, the effect of prophylactic intracameral lidocaine-epinephrine on the incidence, and the relationship between preoperative dilated pupil diameter and the incidence. Tertiary care hospital, Seattle, Washington, USA. Charts of consecutive patients who had cataract extraction by resident physicians between January 2005 and July 2008 were reviewed. Operative notes for patients taking tamsulosin at the time of surgery were reviewed. Preoperative dilated pupil diameter; use of prophylactic intracameral lidocaine-epinephrine; and presence of billowing iris, iris prolapse, and pupil constriction were recorded. Intraoperative floppy-iris syndrome was defined as the occurrence of any of the 3 phenomena constituting the syndrome. Review of 1163 charts identified 59 patients (81 eyes) taking tamsulosin at the time of surgery. The overall incidence of IFIS was 29.6%. Of those who received prophylactic intracameral lidocaine-epinephrine, the incidence of IFIS was 38.5%. The incidence of IFIS was 44.8% in eyes with preoperative dilated pupil diameter smaller than 6.5 mm and 21.7% in eyes with a preoperative dilated pupil diameter larger than 6.5 mm. A preoperative dilated pupil diameter smaller than 6.5 mm was significantly associated with IFIS (P = .032). The incidence of IFIS was lower than previously reported. Use of prophylactic intracameral lidocaine-epinephrine did not reduce the incidence of IFIS. A preoperative dilated pupil diameter smaller than 6.5 mm was significantly associated with an increased incidence of IFIS.